2010
DOI: 10.2164/jandrol.108.007021
|View full text |Cite
|
Sign up to set email alerts
|

Viability Tests, Active Caspase‐3 and −7, and Chromatin Structure in Ram Sperm Selected Using the Swim‐Up Procedure

Abstract: Swim-up (SU) is a technique that permits the obtaining of motile sperm. Based on the sperm motility of neat ejaculates, we analyzed functional parameters, cytoplasmic esterases, and mitochondrial dehydrogenases of ram sperm using calcein acetomethylester and resazurin, respectively. Active caspase-3 and -7 and chromatin structure were evaluated in ram sperm before and after the SU process. There were no changes in any of the viability parameters after SU in neat semen samples with less or more than 25% motilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
6
0
7

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 38 publications
4
6
0
7
Order By: Relevance
“…However, the ejaculates of ovine normally present a high percentage of sperm with active caspases [8]. On other hand, presence of active caspases could correlate negatively [25] or not correlate with motility [8] but not correlate with viability [8]. Recently, using FLICA to detect active caspases, we observed intense staining in cytoplasmic droplets of boar [15] and ram sperm (observations not published), a similar observation was reported early for human sperm [14].…”
Section: Discussionsupporting
confidence: 79%
See 4 more Smart Citations
“…However, the ejaculates of ovine normally present a high percentage of sperm with active caspases [8]. On other hand, presence of active caspases could correlate negatively [25] or not correlate with motility [8] but not correlate with viability [8]. Recently, using FLICA to detect active caspases, we observed intense staining in cytoplasmic droplets of boar [15] and ram sperm (observations not published), a similar observation was reported early for human sperm [14].…”
Section: Discussionsupporting
confidence: 79%
“…The site where cytoplasmic constituents leave the maturing sperm is precisely the middle piece [26], and in this site an intense FLICA-staining has been observed for human [14] and boar sperm [15]. In this work we demonstrated that a strong relationship exists between the presence of active caspases and cytoplasmic esterases for the middle region of ovine sperm; however, intriguingly, active caspases could be present in other regions of sperm apparently not associated with the cytoplasmic droplet, such as equatorial and apical sections in head or principal section in tail [8]. In head and principal section we do not observed correlation between presence of active caspases and esterases.…”
Section: Discussionsupporting
confidence: 68%
See 3 more Smart Citations